EFFECT OF ARGUMENT DRIVEN INQUIRY ON SCIENTIFIC REASONING ABILITY ON THE TOPIC OF ATMOSPHERE AND WEATHER OF GRADE 7 STUDENTS: ผลการจัดการเรียนรู้แบบสืบเสาะหาความรู้ที่ขับเคลื่อนด้วยข้อโต้แย้งที่มีต่อความสามารถในการให้เหตุผลเชิงวิทยาศาสตร์ เรื่อง บรรยากาศและลมฟ้าอากาศ ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 - Manthetsawan, Suphansa; Suppapittayaporn, Decha (Journal of Education and Innovation, 2019)
This research was aimed to study the effect of the Argument Driven Inquiry (ADI) on scientific reasoning ability entitled “Atmosphere and Weather” of Grade 7 students at Ngammuangwitthayakom School, Phayao Province. This research was carried out of 25 students was selected by cluster sampling from 2 classes with 49 total students. The research instruments consist of 1) a total of 7 ADI based lesson plans which allows students to practice constructing scientific claims related to the materials and using evidence to articulate scientific reasons to support their claims and 2) the scientific reasoning test which was validated by a number of experienced teachers and was tried out with a similar context group of students and it is found that the reliability is 0.85, the discrimination is above 0.21, and the difficulty lies between 0.21 - 0.61. The analysis of the result, pre and post-test means comparing using Paired Sample t-test, indicates that the students scientific reasoning ability is significantly improved. This is due to the students had been given opportunities to practice constructing scientific claims in different situations and providing scientific reasoning based on scientific evidence.